Can ownership structure improve environmental performance in Chinese manufacturing firms? The moderating effect of financial performance. (10th July 2019) - Liu, Tiansen; Zhang, Yufeng; Liang, Dapeng
Abstract: There is a growing debate on how should Chinese manufacturing firms improve their environmental performance (EP). This paper analyzes the impact of ownership structure (OS, including state ownership property, SOP; ownership concentration, H5; shareholding ratio of the largest and second shareholders, FS; total proportion of stated-owned shares owned by top 10 shareholders, TOP10; proportion of independent directors accounting for all board members, ID) on EP with considering the moderating effect of financial performance measured by net profit rate (NPR) through 1605 firm-year observations. The findings present that the overall EP of Chinese manufacturers is relatively low (The average level is only 25.94% out of the ideal maximum). Both SOP and H5 can significantly improve EP (marginal effects within 8.20%–8.76% and 4.37%–4.44%, respectively), but the impacts of FS, TOP10, and ID are all not significantly positive. Additionally, H5 significantly improves EP (8.90%–9.08%) when TOP10 is higher than its sample average, and SOP significantly improves EP (10.01%–10.86%) when TOP10 is lower than such average. Further, NPR significantly negatively moderates the impact of FS on EP for the full sample and only positively moderates the impact of higher TOP10 on EP. Empirical results enlighten that some OS-related indicators can steadily contribute to EP, and the weak moderating effect of NPR also presents a positive phenomenon that EP is not dominated by financial performance. Accordingly, corporate EP may keep rising based on its prior trend instead of a major volatility in the coming period. Highlights: This paper focuses on the environmental management in Chinese manufacturing firms. Corporate ownership structure (OS) can improve environmental performance (EP). Overall, financial performance (FP) hardly positively moderates the impact of OS on EP. FP plays a better moderating effect in firms that are with more state-owned shares. Our results present the leading effect of state-owned property and large shareholders in EP.